Visualization Analysis of Spatial Characteristics of Traditional Villages in Southeast Shanxi Province - Zhang Yike; Zhang Zixin (SHS Web of Conferences, 2023)
Traditional villages are rich in material and intangible culture, which is the key point of rural revitalization. Their spatial distribution has certain laws and typical characteristics, which is of great value to the current spatial research of traditional villages. Therefore, this paper chooses one of the core gathering areas of three traditional villages, that is southeast Shanxi Province as the research object. The related GIS spatial analysis method is used to study. The results show that: Traditional villages in southeastern Shanxi Province are in a condensed state, mainly concentrated in the southern region and the southern source of Zhuozhang River, the spatial distribution of villages is closely related to rivers and landforms. From the type point of view, mountain traditional villages are the main ones, while hilly and plain traditional villages are in a minority state, and different types of villages have their own unique spatial construction characteristics. Relevant research contents can provide some reference for the related research of traditional villages in southeast Shanxi Province.